2012
DOI: 10.1007/s12016-011-8296-5
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons: Beneficial in Th1 and Detrimental in Th17 Autoimmunity

Abstract: In relapsing remitting multiple sclerosis (RRMS), type I interferon (IFN) is considered immuno-modulatory and recombinant forms of IFN-β are the most prescribed treatment for this disease. However, within the RRMS population, 30–50% of MS patients are nonresponsive to this treatment, and it consistently worsens neuromyelitis optica (NMO) a disease once considered to be a form of RRMS. In contrast to RRMS, type I IFNs have been shown to have properties that drive the inflammatory pathologies in many other autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 69 publications
(71 reference statements)
2
62
0
1
Order By: Relevance
“…Plasmacytoid dendritic cells were the source of type 1 IFN, which was induced by NETosis arising from neutrophil endocytosis of the amyloid fibrils. Production of the type 1 IFN was therapeutic in Th1-induced adoptive transfer EAE, but exacerbated the paralytic signs of Th17-induced disease, consistent with experiments by Axtell et al (3). However, not all amyloidogenic peptides induced equivalent amounts of type 1 IFN.…”
supporting
confidence: 87%
“…Plasmacytoid dendritic cells were the source of type 1 IFN, which was induced by NETosis arising from neutrophil endocytosis of the amyloid fibrils. Production of the type 1 IFN was therapeutic in Th1-induced adoptive transfer EAE, but exacerbated the paralytic signs of Th17-induced disease, consistent with experiments by Axtell et al (3). However, not all amyloidogenic peptides induced equivalent amounts of type 1 IFN.…”
supporting
confidence: 87%
“…IL-4, IL-6, IL-17, and glucocorticoid receptor signalling pathways, primarily related to Th2 and Th17 cells rather than Th1 cells. This may suggest that Th cell balances play a critical role in etiology and pathology of MS, and may even be being factors influencing responses to treatments as suggested for example by Axtell et al [81,82]. A list of biomarker candidates in blood is given in Table 4.…”
Section: Blood Biomarker Candidatesmentioning
confidence: 99%
“…In the first scenario the IFN beta works with a great benefit for the patient, in the latter case IFN beta may not improve the disease course or even may be detrimental. Therefore, Th17 cell and Th1 cytokines in combination are proposed to indicate the immunological type of RRMS and, thus, therapy response [80][81][82][83].…”
Section: Blood Biomarker Candidatesmentioning
confidence: 99%
“…These discrepancies may be attributed to several reasons, such as the production of neutralizing antibodies (NAbs) [26] and/or the elevated levels of endogenous IFN-β and its gene products prior to initiation of treatment [27]. Nonetheless, IFN-βefficacy seems to be altered by the profile of encephalitogenic T helper cells; IFN-β alleviates symptoms in conditions with Th1 bias, whereas it promotes pathology in Th17 mediated disease [28,29]. Finally, it was recently suggested that high levels of serum IL-17F above a threshold prior to IFN-β treatment may also be responsible for the non-responsiveness of MS patients [29,30].…”
Section: 2ifn-β: As First-line Intervention For Msmentioning
confidence: 99%